Digital Marketing Strategy to Increase the Interest of New Students - Ilham Abdul Jalil; Ach. Nurholis Majid (al-Afkar, Journal For Islamic Studies, 2026)
The development of increasingly sophisticated technology has affected people's habits in accessing information, marked by the abandonment of print media by switching to digital media that can be connected to fast and diverse access to information. The use of digital media for Islamic boarding schools is not only a promotional medium, but also a means of da'wah and education for the community. This research uses a qualitative approach, as well as data collection methods in the form of interviews, observations and documentation. The validity checking techniques used in this study are: source triangulation and technique triangulation. The digital strategies used by the Al-Amien Prenduan Islamic Boarding School are personal branding of the Islamic boarding school, alumni ambassador marketing, fast information accessibility, viral content and influencer collaborative marketing. Meanwhile, digital marketing innovations carried out by the Al-Amien Prenduan Islamic Boarding School are in the form of optimizing the use of social media features, websites and interactive social media as well as upgrading human resources and digital media technology.